Pendampingan Persiapan Akreditasi Sekolah di SDN 3 Suralaga - Fauzi, Lalu Muhammad; Gazali, Muhammad; Hayati, Nila; Satriawan, Rody; Wardi, Zaotul; Ibrahim, Malik; Fadilah, Dina; Ahmad, Syukron (Al-Mu'awanah: Jurnal Pengabdian kepada Masyarakat, 2023)
Accreditation is an acknowledgment from an accreditation body that an institution maintains a certain level of educational standards. Educational accreditation is a quality assurance process by which services and operating institutions, or educational programs are evaluated and verified by an external body to determine whether recognized and accepted standards are being met. If standards are met, accredited status is granted by the appropriate agency. To prepare for this it is considered important to provide assistance to every school that needs it, as was done by SDN 3 Suralaga. Assistance is carried out for 2 months, from April to May 2022. Assistance is carried out through 4 stages, namely 1) presentation of accreditation instrument material, 2) discussion and assistance on school readiness for accreditation, 3) physical evidence assistance, 4) preparation of physical evidence and 5) evaluation of sensitivity. The results of the assistance show that 1) the physical evidence prepared by each teacher who is given the task as the person in charge is ready and complete and 2) the school is ready for visitation.